Four-four masihlalisane - newspaper representation of the South African minibus taxi industry in relation to the Bus Rapid Transit (BRT) system - Selekane, Nkosinathi Leonard (My University, 2014)
This study examined the newspaper representation of the South African minibus taxi industry in relation to the roll out of the Bus Rapid Transit/ Integrated Rapid Transit system in 2009. Articles from major newspapers in 2009 were examined in order to understand how the minibus taxi industry was represented. The aim of the study was to add to the body of knowledge on the media’s representation of the black working class in post-apartheid South Africa. The study was undertaken against a backdrop of existing debates on whether the media in South Africa is transforming. The research is theoretically based on Cultural Studies and the Critical Political Economy of the media. The study investigated the way in which twenty newspaper articles represented the minibus taxi industry during the introduction of the Bus Rapid Transit System. Norman Fairclough’s Critical Discourse Analysis was used to analyse the content of the newspaper articles. The study only focused on English newspapers and did not investigate news from other media, such as the radio and television. A further limitation was the sample size, which was small in comparison to the number of articles that were published on the Bus Rapid Transit System in 2009. The findings revealed that the media continues to perpetuate negative stereotypes of the minibus taxi industry. Future research should include the analysis of images through semiotics and expand the research topic to include the taxi recapitalisation project and road safety. A larger sample should also be used to study the representation of the minibus taxi industry in South African media.